NTS2-selective neurotensin mimetics with tetrahydrofuran amino acids - Simeth, Nadja A.; Bause, Manuel; Dobmeier, Michael; Kling, Ralf; Lachmann, Daniel; Hübner, Harald; Einsiedel, Jürgen; Gmeiner, Peter; Koenig, Burkhard (Bioorganic & Medicinal Chemistry, 2017)
Stimulation of the NTS2 neurotensin receptor causes antipsychotic effects and leads to a promotion of the l-opioid-independent antinociception, which is important in the modulation of tonic pain sensitivity. We report the synthesis and properties of a small library of peptidic agonists based on the active neurotensin fragment NT(8-13). Two tetrahydrofuran amino acid derivatives were synthesized to replace Tyr(11) in NT (8-13). Additionally, Arg(8), Arg(9), and Ile(12) of the lead peptide were exchanged by Lys, Lys, and Gly, respectively. The new compounds showed substantial NTS2 binding affinity and up to 1000-fold selectivity over NTS1. The highest selectivity (Ki(NTS2): 29 nM, Ki(NTS1): 35,000 nM) was observed for the peptide analog 17(Rtrans). (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Neurotensin; Peptides; Non-natural amino acid